Prone versus prone-flexed position in percutaneous nephrolithotomy: A randomized controlled trial - Diaa-Eldin Taha; Ali Ibrahim; Ahmed Zeid; Eslam Shokry; Tarek Abdelbaky; Hossam Nabeeh (Urology Annals)
Background: The aim of this study intends to assess prone and flexed prone positions for percutaneous nephrolithotomy (PNL) for safety and efficacy. Methods: From May 2017 to August 2022, a stratified randomized approach was carried out to randomly assign 346 PNL candidates into prone or flexed prone groups. Perioperative data, such as stone-free rate, stay length, operative time, and complication rates, were studied. Results: In the prone and flexed prone groups, the mean ages of 51.7 ± 12.2 and 49.4 ± 11.9 min, respectively (P = 0.1). The mean body mass indexes of 24.2 ± 13.4 and 29.9 ± 11.9, respectively (P = 0.03). The pyelocaliceal perforation occurred in 15 (8%) and 11 (6.4%) participants, respectively. In the prone and flexed prone postures, postoperative bleeding occurred in 15 (7.9%) and 9 (5.4%) patients, respectively (P = 1.0). The average percentage decrease in hemoglobin concentration was 1.29 ± 0.42 and 1.21 ± 0.32, respectively (P < 0.000). The success rates were 92 and 93.6%, respectively (P = 0.6). The average access length was 3.9 ± 1.2 and 4.8 ± 1.8 min (P = 0.08), whereas the average operation duration was 68.7 ± 37.4 and 50.4 ± 21.9 min (P = 0.04). Conclusion: Both the prone and prone-flexed positions are equally safe for PNL. The flexed prone position is more likely to be beneficial for obese patients. The prone-flexed position enabled a somewhat shorter average operation time. The pelvicalyceal system could be more readily reached when the prone position was flexed.